Teachers’ Confidence in Teaching English Using You*Tube Channel in Early Pandemic Covid-19 - Ketut Santi Indriani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to identify teachers' confidence in teaching English using a You*Tube channel in early pandemic. This study used a qualitative quantitative approach with a survey method. The data sources in this study were 50 teachers from both public and private primary schools in Denpasar who used You*Tube channel as the media in teaching English. The data were collected through questionnaires consisting of 30 closed and open statements which were grouped into four categories. Closed statements consisted of yes/no statements as well as agreement and frequency statements based on a Likert’s five-point scaling. Open statements were intended to provide additional information on the answers to the closed statements that had been given. The data were analyzed qualitatively and presented descriptively using narration supported by diagrams and tables. The result of analysis data showed that teachers' confidence in teaching English using a YouTube channel in the early  pandemic was supported by many factors, such as educational background, teaching experience and teacher perspective in online English learning using the You*Tube channel. However, teaching English through the You*Tube channel needs to be used frequently to improve teachers' skills and techniques in using this media for better teaching.